Muscle activity during maximal isometric forearm rotation using a power grip - Bader, J.; Boland, M. R.; Greybe, D.; Nitz, A.; Uhl, T.; Pienkowski, D. (Journal of Biomechanics, 2018)
This study aimed to provide quantitative activation data for muscles of the forearm during pronation and supination while using a power grip. Electromyographic data was collected from 15 forearm muscles in 11 subjects while they performed maximal isometric pronating and supinating efforts in nine positions of forearm rotation. Biceps brachii was the only muscle with substantial activation in only one effort direction. It was significantly more active when supinating (µ = 52.1%, SD = 17.5%) than pronating (µ = 5.1%, SD =?4.8%, p < .001). All other muscles showed considerable muscle activity during both pronation and supination. Brachioradialis, flexor carpi radialis, palmaris longus, pronator quadratus and pronator teres were significantly more active when pronating the forearm. Abductor pollicis longus and biceps brachii were significantly more active when supinating. This data highlights the importance of including muscles additional to the primary forearm rotators in a biomechanical analysis of forearm rotation. Doing so will further our understanding of forearm function and lead to the improved treatment of forearm fractures, trauma-induced muscle dysfunction and joint replacements.